Clinical features and genetic spectrum of children with primary ciliary dyskinesia in central China: a referral center retrospective analysis - Zhang, Xiaoning; Jin, Xiuhong; Zhang, Zhiying; Wang, Yanqiong; Zhang, Xiangfeng; Dong, Zhen; Yang, Haiming; Shen, Yuelin (Frontiers in Pharmacology, 2025)
BackgroundDespite growing awareness of primary ciliary dyskinesia (PCD) in northern China, few cases have been reported in central China, the most populous region in the country. This study aimed to describe the clinical phenotype and genotype of children with PCD in central China.MethodsWe retrospectively recruited 15 patients with PCD from January 2018 to July 2024. The demographic data, clinical characteristics, laboratory and imaging findings were reviewed to clarify the clinical features. Whole exome sequencing was conducted to identify the genotype.ResultsThe mean age at diagnosis was 8.2 ± 4.8 years. All 15 patients (100%) experienced recurrent wet cough; 93.3% (14/15) had sinusitis, 80.0% (12/15) had otitis media, and 46.7% (7/15) had neonatal respiratory distress. Chest computed tomography revealed that 93.3% (14/15) had nodular shadows and tree-in-bud signs, and 80.0% (12/15) had varying degrees of bronchiectasis. The most common pathogen in the airway was Haemophilus influenzae (9/15, 60.0%). The genes with the highest incidence of variants were DNAH5 (6/13), followed by DNAH11 (3/13). The DNAAF2, DNAH9, DNAAF6, and DNAAF3 genes each were mutated once. Fifteen novel variants were identified.ConclusionPCD is underdiagnosed in central China. The phenotype is characterized by a significant male predominance. Additionally, the incidence of neonatal respiratory distress and situs inversus is notably lower compared to Western countries. The most frequently identified gene responsible for PCD was DNAH5.